PENGARUH MEDIA UNO STACKO TERHADAP KEMAMPUAN HOTS MATERI DIAGRAM BATANG PADA SD NEGERI 81 PALEMBANG - Firmansyah, Rahmat; Misdalina Misdalina; Bz Septeiyawan Abdullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low ability of higher order thinking skills (HOTS) of fourth grade students at SD Negeri 81 Palembang, especially in mathematics material regarding bar diagrams, which is caused by the use of learning media that tends to be monotonous and less interactive. The purpose of this study was to determine whether there is an effect of the use of Uno Stacko media on the HOTS ability of fourth grade students on bar diagram material at SD Negeri 81 Palembang. The research method used is a quantitative approach with a quasi-experimental method (True-experiment) and a posttest-only control group design. The study population includes all fourth grade students, with samples taken using a random sampling technique of 25 students of class IV.A as the experimental class) and 25 students of class IV.E as the control class. Based on the Independent Samples t-Test, a significance value (Sig. 2-tailed) was obtained which was smaller than the significance level (0.000 <0.025). Thus, it can be concluded that the use of Uno Stacko media has a positive and significant effect on students' Higher Order Thinking Skills (HOTS) abilities in bar diagram material in grade IV of SD Negeri 81 Palembang. This media is effective in creating an active, interactive, and enjoyable learning atmosphere for students.